A new monospecific ovine Fab fragment antivenom for treatment of envenoming by the Sri Lankan Russell's viper (Daboia Russelii Russelii): a preliminary dose-finding and pharmacokinetic study. - Ariaratnam, C; Meyer, W; Perera, G; Eddleston, M; Kuleratne, SA; Attapattu, W; Sheriff, R; Richards, A; Theakston, R; Warrell, D (1999)
Russell's viper is the most important cause of life-threatening snake bite and acute renal failure in Sri Lanka. Only equine polyspecific antivenoms imported from India are available. They have not proved effective clinically or in clearing venom antigenemia and they frequently cause reactions. In an attempt to reduce mortality and morbidity, a new monospecific ovine Fab fragment antivenom (PolongaTab; Therapeutic Antibodies, Inc., London, United Kingdom) was raised against Sri Lankan Russell's viper venom. In a preliminary dose-finding study in 35 patients, an initial dose of 3-4 g restored blood coagulability permanently and stopped systemic bleeding, even in severely envenomed patients. Venom antigenemia disappeared within 1 hr of antivenom treatment but recurred, probably as a result of continued absorption of venom from the site of the bite, after the rapid clearance of therapeutic antibody. Twelve patients (34%) experienced early reactions that were usually mild and always responded to epinephrine.